Gambaran puncak kasus demam berdarah dengue di Wilayah utara dan selatan kota sukabumi tahun 2012 - Roy Nusa Rahagus Edo Santya; ohmansyah Wahyu Nurindra (Loka Litbang Kesehatan Pangandaran, 2013)
Incidence of dengue virus infection in Sukabumi city is still as major public health problem because of its case, its distribution, and occurs almost throughout the year. Geographically, Sukabumi city located in mountainous landscape with vary altitude among regions. Based on dengue incidence data reported by Health District of Sukabumi, tracking and plotting patient location and time of the incident was conducted in 2012. Also, the incidence in each village and months was determined. Result shows that there were difference peaks of cases in the northern region where the cases mostly occur in the second half and at the end of the year. Whereas, in Southern region mostly occurred in early first half of the year. North-South division was determined based on altitude differences which Northern-Southern part of Sukabumi city has altitude range that relatively consistent than Western–Eastern part of this city. It concludes that pattern of dengue case was different between the Northern and the Southern part of the city. This condition requires a specific approach to cope dengue case in every region of the city